"Anybody can do science if they're brave enough": Understanding the role of science capital in science majors' identity trajectories into and through postsecondary science. Issue 8 (13th May 2021) - Gonsalves, Allison J.; Cavalcante, Alexandre Soares; Sprowls, Emily Diane; Iacono, Hailey
Abstract: This article reports on research investigating the experiences and resources that make science thinkable for undergraduate science majors as they engage in postsecondary science contexts. We regard these experiences and resources as contributing to science majors' science capital, and we suggest that science capital accumulates over time across identity trajectories . Using a multiple case study approach, we characterize seven undergraduate science majors' identity trajectories that they narrate through their stories of experiences with science in school, out of school and into postsecondary education. We examine how they navigate sources of science capital (e.g., families, science outreach), and the value they attribute to their science capital once they enter science programs in university. We also consider how their access to science capital influences their reasons for engaging in science outreach. To characterize students' movements into postsecondary education, and their experiences in postsecondary science, we crafted three identity trajectories: the "expected trajectory, " "persistent trajectory" and the "new directions trajectory." These trajectories helped us to examine how science majors' identities mediate their perceptions of the use and exchange values of their science capital and the doxa of science that they legitimate. This study contributes to our understanding of how science capital operates along identity trajectories into postsecondary science, and demonstrates that simply having access to resources that contribute to students' accumulation of science capital is not sufficient for sustained engagement in science.